2022
DOI: 10.3389/fpubh.2022.924676
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Knowledge Structure and Global Research Trends in Gout: A Bibliometric Analysis From 2001 to 2021

Abstract: BackgroundThe incidence and prevalence of gout have been steadily increasing globally, which has resulted in gout research attracting consistently increased attention. This study aimed to visualize the knowledge structure and research trends in gout research through bibliometrics to help understand the future development of basic and clinical research.MethodsArticles and reviews on gout from 2001 to 2021 were extracted from the Web of Science Core Collection database. CiteSpace and VOSviewer software were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 61 publications
0
23
0
1
Order By: Relevance
“…Improvements in the national economic level and increases in population are closely correlated with the number of publications in this field. 19,21 We found that almost all major contributors to research in this field are high-income countries, except for China, which is an upper-middle-income country.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Improvements in the national economic level and increases in population are closely correlated with the number of publications in this field. 19,21 We found that almost all major contributors to research in this field are high-income countries, except for China, which is an upper-middle-income country.…”
Section: Discussionmentioning
confidence: 91%
“…The literature cocitation network diagram in Figure 4A was divided into 20 clusters (Supporting Information S1: Figure ). Because the logarithmic likelihood can better cover the “uniqueness and coverage” of all labels, these clusters were labeled by extracting terms from the titles of the referenced publications 21,23,24 . The #0 autopsy study was the largest cluster, followed by #2 antisynthetase syndrome and #3 clinical association.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…4 Theincidenceratesofgoutper100 000populationin2017 (percentagechangebetween1990and2017)wereasfollows:84.9 (6.2) in East Asia, 90.4 (1.7) in South Asia, 88.5 (6.5) in Southeast Asiaand166.4(11.1)inAustralasia.Despitethehighgoutburden, peoplewithgoutlivinginAsia-Pacificcountrieshavebeenrelatively under-represented in gout research. 5 This means that knowledge about gout and how to manage it have been largely derived from studiesconductedamongpopulationsoutsideAsia-Pacificregions. 6 Asia-Pacificisahighlydiverseplaceintermsofethnicities,cultures, comorbidities, and healthcare systems.…”
mentioning
confidence: 99%